Scene : een blad over hiv, leven, liefde en homolifestyle. (Amsterdam : SAD-Schorerstichting, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit: wisselend
Redactie: PC Hooftstraat 5, 1071 BL Amsterdam
Nederlands
Periodiek